ANALISIS VEGETASI PADA SAVANA TANPA TEGAKAN AKASIA (Acacia nilotica) DI TAMAN NASIONAL BALURAN JAWA TIMUR - Djufri Djufri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
The objectives of the research were: (1) to determine the distribution pattern, association, and interaction of plant species, and (2) to determine the relationship between life form and the distribution pattern of species. Quadrate method was used in this research. Determination of species distribution pattern was calculated using Poisson Distribution formula. The result indicated that: (1) The species richness were dominated by grasses, reaching 20,63% of the 33 observed species,  21 of them were in a clumped distribution, 7 species in a reguler, and 5 species were at random pattern. (2) There are relationship between life form and the distribution of the plant species. The multy-plants tend to have a clumped distribution pattern, and single plant tend to heve a reguler or random distribution pattern.